Pemberdayaan Guru dalam Meningkatkan Minat Kewirausahaan Siswa - Arita Marini; Endang Wahyudiana; Arifin Maksum; Julius Sagita; Sri Nuraini; Taufik Rihatno; Endang Kurnianti; Juhana Sakmal; Muril Zahari (Universitas 45 Surabaya, 2024)
Empowering groups of teachers in increasing students' interest in entrepreneurship can provide guidance for students, so that students become interested in entrepreneurship from an early age. Students can develop creativity and entrepreneurial culture, as well as open their minds about future opportunities, be sensitive to community needs, and become skilled problem solvers. The urgency of empowering this group of teachers is that teachers must be able to increase students' entrepreneurial interest so that they are ready to become professional workers full of integrity in the future.